LEADERSHIP STYLE, WORK DISCIPLINE, WORK MOTIVATION TOWARD WORK SATISFACTION AND WORK PRODUCTIVITY AT PT. POS INDONESIA (PERSERO) - Ni Made Dewi Wijayanti Pande (Jurnal Manajemen dan Bisnis, 2014)
Leadership style in an organization held role to influence other party, throughcommunication either directly or indirectly by intend to move people in order to full attention,aware and happy to ready to follow manager willing. By other words that success or not theeffort to reach the organization’s goal determined by quality of leader’s leadership style.Population in this study were all permenent employee in the PT. Pos Indonesia(Persero) branch of Renon Denpasar, there were 206 respondents. Hypotesis test was appliedwith SEM analysis (Structural Equation Modelling) verstion 20.0.The result showed that: (1) leadership style have positive effect and significant towardwork discipline. (2) leadership style have positive effect and significant toward worksatisfaction. (3) leadership style have positive effect and significant toward work productivity.(4) leadership style have positive effect and significant toward work motivation. (5) workdiscipline have positive effect and significant toward work motivation. (6) work discipline havepositive effect and significant toward work satisfaction. (7) work discipline have positive effectand significant toward work productivity. (8) work motivation have positive effect andsignificant toward work discipline. (9) work motivation have positive and significant towardwork productivity. (10) work satisfy have positive and significant toward work productivity.Keywords: Leader, role, position, performance, employee